HUBUNGAN ANTARA PERILAKU MERIAS WAJAH SEHARI-HARI DENGAN KEPERCAYAAN DIRI MAHASISWI RUMPUN PENDIDIKAN KESEJAHTERAAN KELUARGA (PKK) DI UNIVERSITAS NEGERI SURABAYA - Agnessa Rida Cahya Dhea Sindita; Sri Usodoningtyas; Nia Kusstianti; Dindy Sinta Megasari (Jurnal Tata Rias, 2024)
Self-image satisfaction that individuals have is closely related to how individuals view their self-image and self-confidence. Individuals who experience self-image dissatisfaction will appear to engage in behavior related to self-image, namely the efforts made to support their appearance. One of the behaviors that arise is the behavior in applying makeup. This study aims to determine the relationship between daily makeup behavior and self-confidence of female family welfare education students at Surabaya State University and factors that influence daily makeup behavior. Respondents in this study were students of the Family Welfare Education clump at Surabaya State University, class of 2020, consisting of 3 study programs, namely S-1 Cosmetology Education, S-1 Culinary Education, and S-1 Fashion Education. The type of makeup used is everyday makeup. The data analysis technique used was the SPSS-assisted Rank Spearman correlation test. It was found that there was a high positive correlation between daily makeup behavior and self-confidence of female Family Welfare Education students with a correlation coefficient value of 0.879 and a significance value of 0.000 < 0.05. Based on the bivariate analysis of variables, it was found that the factors that influence makeup behavior are internal factors consisting of 1) level of knowledge 2) self-awareness 3) confidence in one's own abilities and external factors, namely environmental factors that stimulate the emergence of daily makeup behavior from the stages of awareness, interest, evaluation, trial, and adoption. The relationship between daily makeup behavior and self-confidence of female Family Welfare Education students at Surabaya State University is positively correlated, which means that if female students increase their daily makeup behavior, their self-confidence will also increase. Keywords: Make Up Behavior, Self-Confidence, Self-Image.